PENGARUH NET PROFIT MARGIN, RETURN ON ASSETS, RETURN ON EQUITY TERHADAP EARNING PER SHARE PADA PT. UNILEVER INDONESIA, Tbk Periode 2005-2013 - Cicih Ratnasih (Fakultas Ekonomi Universitas Borobudur, 2014)
This study aimed to analyze the effect of net profit margin, return on assets, return on equity, to earning Per Share simultaneously and partially on PT Unilever Indonesia. By using current times and series and regression method obtaines results show simultaneous net profit margin, , return on assets, return on equity, to earning Per Share. Partially net profit margin , return on assets, return on equity significantly influence , the Earning Per Share